Pronomina Persona dalam Bahasa Dayak Katingan: Kajian Linguistik Kebudayaan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
Language is an essential part of cultural heritage. This study examines personal pronouns in the Dayak Katingan language spoken in Tewang Darayu Village from a cultural linguistics perspective. Due to limited documentation, this research is considered significant. This study employs a qualitative descriptive approach. Data were collected through interviews with native speakers using emic and etic perspectives, supported by recording techniques. The data were analyzed using a structural approach to identify the forms, functions, and distribution of pronouns, and were further interpreted within the framework of cultural linguistics. The findings reveal distinctive features of the pronominal system, particularly the distinction between dual and plural forms, as well as the use of exclusive and inclusive pronouns. A politeness distinction is also identified. Three cultural values are reflected: participant number distinction, speaker involvement, and politeness strategies. These findings indicate that personal pronouns in Dayak Katingan function not only grammatically but also culturally.